The Influence of Online Marketing on Purchasing Decisions for OMG Lipstick - Teri, Intan Panya Lita; Kundana, Dedi; Taridi, Taridi (LPPM STIAB Jinarakkhita Lampung, 2025)
This study investigates the influence of online marketing on purchasing decisions among young female consumers in the Indonesian urban cosmetics market. Using a quantitative survey approach, data were collected from 70 female respondents aged 16-24 years through a structured questionnaire. The data were analyzed using simple linear regression to examine the impact of social media marketing, particularly on platforms such as Instagram and TikTok, on purchasing behavior. The results show that online marketing has a statistically significant influence on consumer purchasing decisions, with social media promotions playing a significant role in influencing brand awareness and purchase intention. The regression analysis shows a positive relationship between online marketing and purchasing decisions, underscoring the effectiveness of digital platforms in shaping consumer behavior. These findings highlight the importance of strategic data-driven online marketing, particularly for local cosmetic brands targeting Gen Z consumers. This study contributes to the growing literature on digital marketing and consumer behavior in emerging markets, and offers practical implications for marketers seeking to enhance their competitiveness in the digital economy.